PENGARUH AKUNTABILITAS PUBLIK, KEJELASAN SASARAN ANGGARAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Kampar) - Famela Syamratul Aini; Raja Adri Satriawan Surya; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The aim of this study was to examine the Influence of Public Accountability, Clarity of Budget Targets and Organizational Commitment to Managerial Performance in SKPDof Kampar Regency.The location of this research is all SKPD of Kampar. Time research was conducted from May 2015 - November 2015. In this study, the population used is all SKPDof Kampar. Respondents in this study is the structural officials involved in drafting the budget. In total, there are 32 SKPDs. Every SKPD will be given three questionnaires so that the number of questionnaires distributed is 96 pieces. The type of data used are primary data. Data Collection Techniques of field research and literature. The analytical method used in this study is multiple regression analysis.Based on the analysis, the conclusions of this research are: 1) There is a significant influence Public Accountability on Managerial Performance. 2) There is a significant influence the Budget Targets Clarity on Managerial Performance. 3) There is a significant influence Organizational Commitment on Managerial Performance. Based on the research results it was concluded that the determination coefficient 0,559. The coefficient of determination is positive, it indicates that approximately 55.9% of the variation can be explained by the Public Accountability, Clarity of Budget Targets and Organizational Commitment. While the remaining 44.1% is explained by other variables outside the model.Keywords: Public Accountability, Clarity of Target Budget, Organizational Commitment and Managerial Performance